Regional Nanoindentation Properties in Different Locations on the Mouse Tibia From C57BL/6 and Balb/C Female Mice - Pepe, Valentina; Oliviero, Sara; Cristofolini, Luca; Dall'Ara, Enrico (Frontiers in Bioengineering and Biotechnology, 2020)
Little is known about the local material properties of the cortical and trabecular bone extracted from the mouse tibia. The goal of this study was to evaluate the nanoindentation properties of bone tissue extracted from different regions of the tibiae of different mouse strains. Left tibiae were collected from four female mice, two C57BL/6 and two Balb/C mice. 379 nanoindentations with maximum 6mN load were performed on different microstructures, regions along the axis of the tibiae and sectors. Reduced modulus (Er) and hardness (H) were computed for each indentation. Trabecular bone of Balb/C mice was 21% stiffer than that of C57Bl6 mice. Moreover, the proximal regions of the bones were 13% to 36% less stiff than the mid-shaft and distal regions of the same bones. No significant differences were found for the different sectors for Er and H for Balb/C mice. The bone in the medial sector was found to be 8-14% harder and stiffer than the bone in the anterior or posterior sectors for C57BL/6 mice. In conclusion, this study showed that the nanoindentation properties of the mouse tibia are heterogeneous across the tibia length and the trabecular bone properties are different between Balb/C and C57BL/6 mice.